The new way of wasted oils regeneration - Korchak, B. O.; Chervinskiy, T. I.; Hrynyshyn, O. B. (Lviv Polytechnic Publishing House, 2016)
It has been established the possibility of waste mineral engine oil regeneration with thermooxidative method. The influence of temperature, pressure and process duration on the basis of regenerated engine oil has been explored. It has been suggested the using of thermooxidative oil regeneration with absorption and hydrogenation methods.
Keywords: thermooxidative; regeneration; waste oil; mineral engine oil; influence of pressure